Post-traumatic Stress Disorder in Sexually Abused Children: Secure Attachment as a Protective Factor - Ensink, Karin; Fonagy, Peter; Normandin, Lina; Rozenberg, Abby; Marquez, Christina; Godbout, Natacha; Borelli, Jessica L. (Frontiers in Psychology, 2021)
The aim of the present study was to examine the hypothesis that attachment and CSA interacted such that school aged CSA survivors with insecure attachment to parents would be at an elevated risk of developing PTSD and trauma symptoms. Participants (n = 111, ages 7-12) comprised two groups, child CSA survivors (n = 43) and a matched comparison group of children (n = 68) recruited from the community. Children completed the Child Attachment Interview as well as the Trauma Symptom Checklist for Children (TSCC). There was a significant interaction between sexual abuse history and attachment security, such that sexually abused children with insecure attachment representations had significantly more PTSD and trauma symptoms than sexually abused children with secure attachment to parents. The findings show that using a dual lens of attachment and CSA can facilitate identification children most at risk have important implications for understanding risk and resilience processes.